2008
DOI: 10.1073/pnas.0808608105
|View full text |Cite
|
Sign up to set email alerts
|

The potential of desferrioxamine-gallium as an anti- Pseudomonas therapeutic agent

Abstract: The opportunistic pathogen Pseudomonas aeruginosa causes infections that are difficult to treat by antibiotic therapy. This bacterium can cause biofilm infections where it shows tolerance to antibiotics. Here we report the novel use of a metallo-complex, desferrioxaminegallium (DFO-Ga) that targets P. aeruginosa iron metabolism. This complex kills free-living bacteria and blocks biofilm formation. A combination of DFO-Ga and the anti-Pseudomonas antibiotic gentamicin caused massive killing of P. aeruginosa cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
204
0
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 241 publications
(217 citation statements)
references
References 36 publications
7
204
0
6
Order By: Relevance
“…Banin et al [60] have used siderophore-metal complex combining a strong siderophore, DFO with non-radioactive gallium for the treatment of Pseudomonas aeruginosa (P.a.) infection.…”
Section: Siderophores For Molecular Imaging Of Infectionmentioning
confidence: 99%
“…Banin et al [60] have used siderophore-metal complex combining a strong siderophore, DFO with non-radioactive gallium for the treatment of Pseudomonas aeruginosa (P.a.) infection.…”
Section: Siderophores For Molecular Imaging Of Infectionmentioning
confidence: 99%
“…15 In other studies, da Silva et al reported on the effect of the coordination of Ga 3+ on the antibacterial activity of N(4)-phenyl-2-formylpyridine thiosemicarbazone and N(4)-phenyl-2-benzoylpyridine thiosemicarbazone against P. aeruginosa, 16 and Bernstein illustrated how solution chemistry and the versatility of bacterial metabolic networks could increase or decrease the toxicity of Ga for a pathogenic bacterium. 17 In addition to the reports on the activity of Ga ions against P. aeruginosa, 3,14 there are also several recent reports detailing the antibacterial activity of C-dots 18,19 and a C-dot-Ag nanocomposite. 20 However, to the best of our knowledge, no reports on the antibacterial activity of Ga doped in C-dots (Ga@C-dots) have been published.…”
Section: Introductionmentioning
confidence: 99%
“…Есть ряд работ, посвященных ингибированию роста Ps. aeruginosa наряду с биопленкой, форми-руемой этим микроорганизмом, в которых показаны различные пути доставки галлия в бактериальную клетку -использующие нитрит галлия Ga(NO 3 ) 3 [2] и соединение дезферриоксамина с галлием [38]. В по-следнем случае хоть и не был установлен механизм действия антибактериального агента, тем не менее желаемый эффект был достигнут -было отмечено подавле-ние инфекционного процесса, вызванного Ps.…”
Section: разрушение бактериальной клеточной стенки и нарушение внутреunclassified